Transfer of Ownership Rights on House Sale With Installment Method (Case Study of Bekasi District Court Decision Number 124/Pdt.G/2020/PN Bks) - Diva Salsabila Ferdiansyah; Atik Winanti (Dinasti Research, 2024)
Land is a vital natural resource for human life, necessitating adequate legal protection regarding land rights. One mechanism for transferring land rights is through the Sale and Purchase Binding Agreement (PPJB), often used in property transactions such as houses or other real estate. However, in practice, legal issues frequently arise regarding buyer protection, particularly in cases of default. This study aims to analyse the acquisition of ownership rights in house sale and purchase transactions, as exemplified by the Bekasi District Court Decision Number 124/Pdt.G/2020/Pn Bks. Using a normative juridical method with statute approach and case approach, this research examines relevant regulations and their application to the transfer of rights in property transactions. The findings reveal that the court's considerations in this case were inconsistent with Article 22L Paragraph (4) of Government Regulation No. 12 of 2021. Therefore, more equitable legal protection is necessary, referring to the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), to ensure optimal protection for all parties involved in property sale and purchase transactions.